Análisis del control de cuentas por cobrar y su incidencia en la liquidez de la distribuidora Palacios Soto y CIA. APROMED de la ciudad de Loja, en el periodo 2017 - Flores Carrión, María del Cisne (2020)
he thesis work entitled “ANALYSIS OF ACCOUNT OF CONTROL TO BE COLLECTED AND ITS INCIDENCE IN THE LIQUIDITY OF THE DISTRIBUIDORA PALACIOS SOTO Y CIA. APPROVED OF THE CITY OF LOJA, IN THE PERIOD 2017”, is developed to meet the prerequisite to obtain the degree of Engineering in Accounting and Audit, in order to publicize the procedures for managing accounts receivable It manages in the company and also the economic development that can occur in a certain time. The methodology applied for its execution consists of gathering reliable and reliable information, where it is necessary to apply an interview to the president of the Distributor of which a SWOT matrix is required that detect all internal and external aspects that can affect the proper functioning of The company, in order to apply its own procedures for granting loans and recovering its portfolio, determine its liquidity, solvency and activity situation that it has in 2017. For the fulfillment of the stated objectives, a comparative chart of the accounts receivable policies and procedures will be carried out in front of IAS 39, where the non-compliance with the regulations could be observed, and in this way a chart of accounting procedures was also made. of accounts receivable and a flowchart of the activities that the company must fulfill in the accounts receivable process, which is accompanied by a narrative card, that way each of the client accounts with past due portfolio was classified to determine according to the company's policies the maturities that the customers established in the 2017 period. The results 5 obtained are worrisome due to the financial economic situation, in relation to liquidity, a result of $ 0.77 is obtained for each dollar owed, which shows that it has no capacity to cover its obligations without depending on its inventories, thus You can prove that the over-indebtedness is 55%, more than half of the company is in the hands of its creditors. It should be taken into account that the excessive purchase of materials could lead to problems in the future with the stoppage of merchandise, which would lead to a loss, where you can take into account the return policies of the companies from which the goods are acquired, products.